Simulation of 3D-Microstructure in Free-cutting Steel 9SMn28 under Water Cooling Condition with Convection and Porosity - Wang, Fuming; Li, Changrong; Zhang, Jiongming; Wang, Jinlong (ISIJ International, 2010)
The 3D-microstructure in 9SMn28 free-cutting steel under water cooling condition was simulated based on the finite element–cellular automaton method with convection and porosity, and the simulated results are consistent with that of the experiment. The casting of 9SMn28 alloy is a stepwise solidification mode under water cooling condition. Convection is mainly made of buoyancy-driven flows and feeding flows in perpendicular direction of the solid–liquid interface. Convection is the reason of shaggy on free surface; it can decrease pipe shrinkage and columnar grain zone. Flow field plays an importance role in even temperature field and irregulation porosity morphology. The simulated result of pipe shrinkage is consistent with that of this experiment; the simulated result of porosity is identical with that of this experiment basically.